Analysis of the literature pertaining to the education of public health professionals - Connie J Evashwick; Donghua eTao; Kate eBax (Frontiers Media S.A., 2013)
A well-educated workforce is essential to the infrastructure of a public health system. At the time when global focus on public health is increasing, a severe shortage of public health professionals is projected. A strong educational framework is imperative to ensure the capacity and capability of the worldwide public health workforce for the future. Frenk and Chen (2011) comment that academic public health has done far less than medicine or nursing to examine its pedagogy. The goal of this study is to examine the literature pertaining to the education of public health professionals in order to document the extent to which those preparing public health professionals think about what they teach, how they teach, and what the results of the instruction are. The specific objectives are to (1) identify relevant peer reviewed literature, (2) analyze that literature for content, (3) characterize the literature according to type of methodology, and (4) draw conclusions and implications to enhance future pedagogical efforts. The study searched three bibliographic sources for articles written in English between 2000-2012. The search of PubMed, Scopus, Education Full Text identified 576 unique articles. The articles were analyzed according to ten content themes and four format categories. The conclusions are that those teaching public health professionals devote considerable thought to what and how they teach, although original research and evaluation studies are fewer than descriptive reports of courses, programs and curricula. A journal devoted specifically to articles pertaining to education of public health professionals will encourage academicians to write articles sharing approaches to educating the public health workforce.